THE HELMINTH PARASITES OF RATTUS RATTUS (LINNAEUS, 1758) OF URBAN, INTERMEDIATE AND RURAL ENVIRONMENTS IN SOUTHERN BRAZIL - Oliveira de Araujo, Eduardo (2014)
Rattus rattus has synanthropic habits which make it an important rodent for the dissemination of zoonotic parasites. Thirty individuals were captured and necropsied with the aim of knowing theie helminth fauna. Three species of parasites were found, two nematodes (Aspiculuris tetraptera and Syphacia obvelata) and one cestode (Hymenolepis diminuta). The rural area showed most diversity of helminthes.